Usage of Surfactant and Evaluation of Lung Problems in Late Preterm Infants - Yilman, Ozlem; Alkan Ozdemir, Senem; Calkavur, Sebnem; Gokmen Yildirim , Tulin (Gynecology Obstetrics & Reproductive Medicine, 2023)
OBJECTIVE: We aimed to evaluate surfactant frequency and surfactant indications, as well as lung problems in late preterm infants. STUDY DESIGN: This retrospective and cross-sectional study was carried out by HSU Izmir Dr. Behcet Uz Pediatric Diseases and Surgery Research and Training Hospital. Infants who were born late preterm between January 2016 and January 2022 were hospitalized in the NICU due to respiratory distress in the first 24 hours. Lung problems and surfactant administration of these infants were evaluated. The frequency of surfactant dosages, their indications, and their effects were examined. As the control group, patients who were admitted to the NICU in the same period due to respiratory distress with similar indications but did not receive surfactant were considered. RESULTS: It was observed that surfactant was not administered to 105 infants and surfactant was administered to 106 infants. The median gestational week of the infants included in the study was 35 (34/36) weeks and the birth weight was 2185 (1780/2590) grams. A significant difference was observed in birth weight between the groups (p<0.001). Invasive ventilation was required in 52.1% of all cases and noninvasive ventilation was required in 33.6%. In the delivery room, the need for resuscitation and intubation was higher in the group requiring surfactant (p=0.001). The most common lung pathology in the surfactant group was RDS. CONCLUSION: It must not be forgotten that infants who are born late preterm infants are preterm infants and the evaluation of antenatal steroid administration must not be ignored.